Otherness and stigma: The public understanding of what mental illness is moderates the association of continuum beliefs and social acceptance - Vanessa Juergensen; Mirjam Göbel; Bruce G. Link; Vincent Buckwitz; Georg Schomerus; Sven Speerforck (Elsevier, 2024)
Belief in a continuum of symptoms from mental health to mental illness (MI) has an impact on the social acceptance of people with MI. However, little is known about whether people's conception of MI itself and in particular how broad that conception is, has an impact on the social acceptance of individuals with MI or affects continuum beliefs. To address this research gap, it is necessary to capture and monitor public understanding of MI. Using 17 different statements that describe behaviors on a spectrum from mentally healthy to ambiguous to indicative of MI, we examine how the German public conceptualizes MI. Specifically, we develop a measure to capture the breadth of an individual's conception of MI. We find that a broader concept of MI is associated with greater social acceptability. In addition, we show that continuum beliefs and the breadth of the concept of MI interact - continuum beliefs are especially important for stigma reduction when individuals have a narrow concept of MI. For future research, this finding implies that with regard to social acceptance of people with MI, individuals with a narrow concept benefit from continuum interventions in particular.